Essentials of Chinese Medicine - Liu, Zhanwen (Springer London : Imprint: Springer, 2010)
The modern medical model is gradually shifting from one of biomedicine to one that integrates practices from the physiological, psychological, sociological and medical fields. This growing recognition that people, the environment, ecological conditions and society are all aspects of a united whole has given rise to an emergence of alternative medicine and therapies, many of which are borrowed from traditional Chinese medicine. Essentials of Chinese Medicine systematically introduces the basic theories, diagnostic methods, therapeutic practices, and the principles of health preservation and rehabilitation of the Chinese medical tradition. The basic theories and methods of acupuncture and moxibustion are explained, and a range of Chinese herbs are illustrated. The textbooks also introduces 84 Chinese herbal formulas and 6 associated formulas commonly used in clinical practice. Furthermore, it elucidates treatments of commonly and frequently encountered diseases in internal medicine, surgery, gynecology, pediatrics, ophthalmology and otorhinolaryngology. With a strong emphasis on the fundamental principles of Chinese Medicine, this three-volume set provides concise and systematic content that is suitable for both teaching and self-study.